In Figure-2, ABC is an isosceles
s triangle, right-angled at C. Therefore
(A), AB2=2AC2
(B) BC2 = 2AB2
(C) AC2 = 2AB2
(D) AB2= 4AC2
AC AAC
AB²
(2A CZ
Figure-2
Attachments:
![](https://hi-static.z-dn.net/files/d15/5c5199594fd8655c93e7fa827cd6ffe0.jpg)
Answers
Answered by
5
Step-by-step explanation:
Hope it will helped you . If it is so mark me as brainlist....
Attachments:
![](https://hi-static.z-dn.net/files/d88/72f86af4816a58d65b3ce1ef438d150b.jpg)
Answered by
2
Answer:
(A), AB^2=2*AC^2.
Explanation:
By Pythagoras theorem,
AB^2=AC^2 + BC^2
AB^2=AC^2 + AC^2 [BC=AC, ISOCELES TRIANGLE]
AB^2=2*AC^2[PROVED]
Similar questions